ثقافة الميمز في األوساط الرقمية (فن الكاريكاتور أنموذجا ) - دريسي خضرة (My University, 2026)
This study concludes that "meme culture" represents the digital, interactive, and democratic extension of traditional journalistic caricature within the new communication environment. Memes have successfully shifted the power of satirical expression and social critique from the elite and professional cartoonists to the average user across social media platforms. Semiotic and communication analysis of the study's sample demonstrates that memes are not merely tools for transient digital entertainment; rather, they constitute a significant sociological phenomenon and a powerful instrument for "cultural and political resistance" and social catharsis. Characterized by a phenomenal capacity for viral propagation and instant reproduction to keep pace with current events, their effectiveness relies entirely on a shared cultural and symbolic context between the meme creator and the audience. Consequently, memes collectively forge a virtual collective consciousness that reshapes public opinion and dismantles the barriers of traditional censorship in the digital sphere ------------------ تخلص هذه الدراسة إلى أن "ثقافة الميمز" (Memes) تُمثل الامتداد الرقمي، التفاعلي، والديمقراطي لفن الكاريكاتير الصحفي التقليدي في البيئة الاتصالية الجديدة؛ حيث نجحت الميمز في نقل سلطة التعبير والنقد الساخر من "النخبة والرسام المحترف" إلى "المستخدم العادي" عبر منصات التواصل الاجتماعي. وقد أثبت التحليل السيميائي والاتصالي لعينة الدراسة أن الميمز ليست مجرد أدوات للتسلية الرقمية العابرة، بل هي ظاهرة سوسيولوجية وازنة وأداة قوية لـ "المقاومة الثقافية والسياسية" والتنفيس الاجتماعي، تتميز بقدرة فائقة على الانتشار الفيروسي وإعادة الإنتاج الفوري لمواكبة الأحداث الراهنة. وترتبط فاعليتها بوجود سياق ثقافي ورمزي مشترك بين صانع الميم ومتلقّيه، مما يجعلها تشكل في مجموعها وعياً جمعياً افتراضياً يعيد صياغة الرأي العام ويكسر حواجز الرقابة التقليدية في الفضاء الرقمي. ---------------- Cette étude conclut que la "culture des mèmes" (Memes) représente l'extension numérique, interactive et démocratique de la caricature journalistique traditionnelle dans le nouvel environnement communicationnel. Les mèmes ont réussi à transférer le pouvoir de l'expression et de la critique satirique de l'élite et des caricaturistes professionnels vers l'utilisateur ordinaire sur les réseaux sociaux. L'analyse sémiotique et communicationnelle du corpus montre que les mèmes ne sont pas de simples outils de divertissement éphémères, mais plutôt un phénomène sociologique majeur et un puissant instrument de "résistance culturelle et politique" et de catharsis sociale. Ils se caractérisent par une capacité phénoménale de propagation virale et de réadaptation instantanée pour suivre l'actualité. Leur efficacité demeure toutefois conditionnée par l'existence d'un contexte culturel et symbolique partagé entre le créateur du mème et son public, ce qui leur permet de façonner une conscience collective virtuelle capable de modeler l'opinion publique et de briser les barrières de la censure traditionnelle dans l'espace numérique
Keywords: Caricature; Memes; Digital environments; Semiology; الكاريكاتور، الميمز، الاوساط الرقمية، السيميولوجيا; Mèmes; Environnements numériques; Sémiologie